2019
DOI: 10.1002/cam4.1954
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy after surgery has significant survival benefits for patients with triple‐negative breast cancer

Abstract: Objectives The value of adjuvant radiotherapy for triple‐negative breast cancer (TNBC) has been controversial recently. This study aims to clarify the influence of radiotherapy on the survival of TNBC patients after surgery based on a large population analysis. Methods The Surveillance, Epidemiology, and End Results (SEER) database was exploited to select eligible patients from 2010 to 2014. The categorical variables were examined by chi‐square tests. Breast cancer‐specific survival (BCSS) and overall survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 12 publications
5
29
0
Order By: Relevance
“…A report from CCO highlights that in Ontario, the majority of women with BC are receiving surgical treatment within the recommended time from diagnosis, which is 28 days for invasive but not highly aggressive malignancy. 34 The adjuvant treatment rate in our study aligns with similar contemporary cohorts 14,35 and was initiated at a median of 44 days after surgery. However, recent studies [36][37][38] have shown improved outcomes in TNBC patients starting AT within 30 days, highlighting a critical opportunity for improvement.…”
Section: Treatmentsupporting
confidence: 71%
See 2 more Smart Citations
“…A report from CCO highlights that in Ontario, the majority of women with BC are receiving surgical treatment within the recommended time from diagnosis, which is 28 days for invasive but not highly aggressive malignancy. 34 The adjuvant treatment rate in our study aligns with similar contemporary cohorts 14,35 and was initiated at a median of 44 days after surgery. However, recent studies [36][37][38] have shown improved outcomes in TNBC patients starting AT within 30 days, highlighting a critical opportunity for improvement.…”
Section: Treatmentsupporting
confidence: 71%
“…This is similar to a Swiss study 13 and significantly higher than other reported rates of around 48%. 7,14,35 This is a positive observation considering the survival benefit of adjuvant RT seen in a Danish study 42 and a more recent confirmative population-based study. 35 The rate of exposure to systemic therapy in our cohort (80% in stage I-III and 73% in stage IV) was similar to or better than many similar populations.…”
Section: Treatmentmentioning
confidence: 80%
See 1 more Smart Citation
“…To our knowledge, limited data are reported regarding the IR-induced gene expression changes in relation to BC tumor grading (20)(21)(22)(23)(24). In this sense, we recently reported IRinduced low grade-and high grade-specific signaling in BC cells (5).…”
mentioning
confidence: 96%
“…In addition, the absence of hormonal or targeted therapy against TNBC makes it a clinical challenge for oncologists in terms of patient management. However, Yao and colleagues have recently reported a survival advantage of adjuvant RT for TNBC patients, underling the necessity to study and clarify molecular mechanisms active in these cells and how these are involved in regulating cell survival/death balance (24).…”
mentioning
confidence: 99%